Exploring extracellular vesicles as novel therapeutic agents for intervertebral disc degeneration: delivery, applications, and mechanisms - Yuxin Jin; Ouqiang Wu; Zhihua Chen; Linjie Chen; Kai Zhang; Qizhu Chen; Haijun Tian; Xinzhou Wang; Morgan Jones; Kenny Yat Hong Kwan; Yan Michael Li; Pooyan Makvandi; et al. (Stem Cell Research & Therapy)
Abstract Intervertebral disc degeneration is a multifactorial degenerative disease that poses a significant threat to the health of the elderly population. Current treatments primarily focus on physical therapy, medication, and surgery to alleviate symptoms associated with disc compression but do not address the progression of degeneration. Therefore, this review aimed to explore the potential of extracellular vesicle therapy as a novel preventive strategy to delay degeneration and enhance tissue repair in intervertebral discs. We cover the pathogenic mechanisms underlying intervertebral disc degeneration, including inflammation, apoptosis, pyroptosis, ferroptosis, autophagy dysregulation, and the roles of non-coding RNAs. Subsequently, we discussed the therapeutic potential of extracellular vesicles and their molecular components, such as proteins, RNAs, and lipids, in modulating these pathways to counter intervertebral disc degeneration. We provides a comprehensive review of the significant role of extracellular vesicle cargo in mediating repair mechanisms. It discusses the functional enhancement advantages exhibited by extracellular vesicles under current bioengineering modifications and drug loading. The challenges and future prospects of utilizing extracellular vesicle therapy to treat this degenerative condition are also summarized. Graphical abstract